In Memoriam - Miriam Hederman O’Brien - Remarks on the Occasion of the Launch of the Online Archive of the Journal of the Statistical and Social Inquiry Society of Ireland - Hederman O'Brien, Miriam (Statistical and Social Inquiry Society of Ireland, 2022)
EDITOR’S NOTE: The late Dr Miriam Hederman O’Brien (1932-2022) joined the Council of the Society in 1988 and became Vice President in 2005. In her honour we publish her speech made on 16th May 2007 in the Long Room of the Library of Trinity College Dublin on the occasion of the launch of the Journal of the Statistical and Social Inquiry Society of Ireland’s online archive.
EDITOR’S NOTE: The late Dr Miriam Hederman O’Brien (1932-2022) joined the Council of the Society in 1988 and became Vice President in 2005. In her honour we publish her speech made on 16th May 2007 in the Long Room of the Library of Trinity College Dublin on the occasion of the launch of the Journal of the Statistical and Social Inquiry Society of Ireland’s online archive.
Keywords: Miriam Hederman O'Brien; 314.15